2003
DOI: 10.1097/01.smj.0000051268.43410.45
|View full text |Cite
|
Sign up to set email alerts
|

Personal Breast-feeding Behaviors of Female Physicians in Mississippi

Abstract: The breast-feeding initiation rates among female physicians surpassed those of women in the general population, yet duration rates were comparable. Their own breast-feeding success might enhance the potential of female physicians as advocates and sources of credible information regarding breast-feeding; however, physicians need to be better educated regarding the management of breast-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 11 publications
4
30
1
2
Order By: Relevance
“…Key obstacles include the return, after maternity leave, to the rigorous work schedule of residency or primary care practice, as well as inadequate support for milk expression in the workplace. [4][5][6][7] Describing physicians' experiences is important from two perspectives. First, physicians' own experiences in breastfeeding their children may adversely affect their future interactions with breastfeeding mothers who are patients.…”
Section: Introductionmentioning
confidence: 99%
“…Key obstacles include the return, after maternity leave, to the rigorous work schedule of residency or primary care practice, as well as inadequate support for milk expression in the workplace. [4][5][6][7] Describing physicians' experiences is important from two perspectives. First, physicians' own experiences in breastfeeding their children may adversely affect their future interactions with breastfeeding mothers who are patients.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Physician mothers who attempt to maintain breastfeeding after maternity leave identify two main obstacles at work: lack of sufficient time and adequate place for milk expression. [12][13][14] Similarly, physician mothers' main reasons for breastfeeding cessation, especially between 1 and 12 months postpartum, are work-related.…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted prior to the 80-hour work week mandate, 6-month continuation rates ranged from 15% to 21%. [13][14][15] A more recent study with a smaller sample size found a 6-month continuation rate of 58% among female obstetrics-gynecology and family medicine housestaff in one institution in the post-80-hour work week era. 16 The difference in 6-month continuation rates could be due to differences in sample sizes or be a reflection of impact of maternal work hours on breastfeeding duration.…”
Section: Importance Of Studying Breastfeeding Among Physiciansmentioning
confidence: 99%
“…To date, our understanding of breastfeeding among physicians in the United States has been based on cross-sectional questionnaire surveys administered to residents and/or practicing physicians. [13][14][15][16] According to these studies, breastfeeding initiation rates among female physicians ranged from 80% to 94%, exceeding the HP2010 goals (Table 1). However, breastfeeding continuation rates at 6 and 12 months were usually below HP2010 objectives, regardless of whether the group surveyed was still in training or not (Table 1).…”
Section: Importance Of Studying Breastfeeding Among Physiciansmentioning
confidence: 99%